A Step by Step of Content ValidityAssessment Process on Approach Towards Safety Knowledge, Safety Climate and SMEs Safety Performance Framework. - Rahlin, Nor Azma binti; Bahkia, Ayu Suriawaty Siti Aisyah; Awang, Zainudin; Razak, Roslida Abdul; Idris, Sidah (The journal of contemporary issues in business and government, 2021)
This article examines the issues and the conceptual basis in the operationalized definition of safety knowledge. The importance of safety knowledgeemphasizes the mediation role of safety knowledge in the indirect link between safety climate and safety performance assessment in small and medium enterprises and the functional nature of content validity by applying a step-by- stepcontent validity assessment. A content validation assessment process aims to increase representativeness, relevancy, clarity, comprehensiveness of the measurement's validitybesides to ensure the instrument answers the research question. In business, social science, and management science, many variables of interest and research outcomes are abstract concepts and its function by robust theoretical and conceptual explanation. Thus, a step-by-stepcontent validity assessment offered a bridge to achieve a valid and reliable measurement, and it was an essential element of quality research.